Process Oriented Guided Inquiry Learning (POGIL) A Learning Model to Developing Basic Science Process Skills in Madrasah Ibtidaiyah - Khotimah, Husnul; Saefuddin, Asis; Marthyane Pratiwi, Inne (Al-Aulad: Journal of Islamic Primary Education, 2025)
The research was driven the lack of student engagement in Natural and Social Sciences subjects, particularly in the areas of communication and clasification, both of which are key components of basic science process skills. This research aims to see the improvement of basic science process skills by applying the POGIL learning model in the subjects of Natural Sciences and Social Sciences in each cycle. Conducted through Classroom Action Research using the Kemmis and Taggart model (planning, acting, observing, and reflecting), the study involved 33 fifth-grade students at MIN 1 Bandung City. Data were collected through observations, performance tests, and descriptive tests. Initial findings showed that students’ basic science process skills were at a "Low" level, with an average score of 60.15 and a classical completeness rate of 30.33% ("Very Poor" category). The POGIL model used in Natural and Social Sciences subjects for the students from the fifth grade was revealed to be effectively implemented over three cycles, as reflected in increasing teacher activity scores (from the pre-cycle 66.67%, cycle I 82.36%, cycle II 94.11%, and cycle III 100%). Meanwhile, the cumulative average of student activity scores also increased (from the pre-cycle 60.10%, cycle 1 66.91%,cycle II 94.11%, and cycle III 88.38%). Additionally, students’ science process skills improved across cycles: 62.72 ("Low") in Cycle I, 70.15 ("Medium") in Cycle II, and 76.96 ("Medium") in Cycle III. These results shows that POGIL model can effectively enhance students’ basic science process skills in Natural and Social Sciences at the Madrasah Ibtidaiyah level.